Factors related to safety riding behaviors among grade XII students of SMKN 3 Mandau Duri - Arianto, Machfudz Eko; Setiaji, Reno (Universitas Ahmad Dahlan, 2023)
Background: The occurrence of traffic accidents is proof that road users are undisciplined in riding. Accident rates among the students of SMKN 3 Mandau Duri reached their highest levels in 2019 and 2022. Based on the information from interviews conducted with 6 students, the causes of the accidents were that they rode without SIM C, three of them mentioned that wearing a helmet was not compulsory, and peers asked them to act unsafely. This study is aimed at finding out the correlation between knowledge, attitudes, possession of SIM C, as well as peers and safety riding behaviors among the Grade XII students of SMKN 3 Mandau Duri. Methods: This study is quantitative in nature using a cross sectional approach. The population of this study consisted of 309 students from which proportional random sampling was applied so that as many as 174 respondents were selected as the samples. The data analysis was executed using univariate and bivariate Chi Square tests. The instrument utilized in this study was the questionnaire from researchers whose validity and reliability have been tested. Results: Correlations were found between knowledge and safety riding behaviors (p-value = 0.006), attitudes and safety riding behaviors (p-value = 0.000), SIM C possession and safety riding behaviors (p-value = 0.000), and peers’ influence and safety riding behaviors (p-value = 0.000). Conclusion: There were correlations between knowledge, attitude, SIM C possession, as well as peers’ influence and safety riding behaviors among the Grade XII students of SMKN 3 Mandau Duri